Precipitation of cellulase and xylanase for cross-linked enzyme aggregates - Sulaiman, Nurul Jannah (2013)
Cross-linked enzyme aggregate is a promising strategy among other enzyme immobilization technologies such as solid matrix linking and gel entrapping. Despite of having the advantage of being reused, cross-linked enzyme aggregate (CLEA) also offers greater stability during operation and storage. Preparation of CLEA involves two steps which are precipitation and cross-linking of the enzymes. The purpose of this study is to find the best precipitant for cross-linked enzyme aggregate of cellulase and xylanase. The tested precipitants were acetone, ammonium sulphate, dimethoxyethane (DME), n-propanol, polyethyleneglycol (PEG), and tert-butanol. The enzymes were precipitated and cross-linked using glutaraldehyde. The enzyme activities were determined through DNS method and the relative activities for resulted CLEA were compared. It was found that PEG was the best precipitant for CLEA-cellulase while DME, ammonium sulphate and tert-butanol contributed the highest activity retention for CLEA-cellulase-xylanase under cellulase and xylanase assay, and CLEA-xylanase, respectively.